Evaluation of kinetic effects of Gliotoxin in different breast cancer cell lines: Effects of Gliotoxin in different breast cancer - Akkülah Şenol, Göksu; Çalişkan, Mahmut; Topçul, Mehmet Rıfkı (Cellular and Molecular Biology, 2023)
In the present research, the antiproliferative properties of Gliotoxin, which is obtained from marine fungus and thought to be a promising metabolite, on MCF-7 and MDA-MB-231 breast cancer cells, which have different molecular subtypes, were evaluated. Different cell kinetic parameters were employed for this aim. In experiments, cell viability, cell index, mitotic index, BrdU labeling index, and apoptotic index were assessed. Gliotoxin concentrations of 1.5625 µM, 3.125 µM, and 6.25 µM were used in studies for both cell lines. As a result of the values obtained from cell viability and xCELLigence Real-Time Cell Analysis (RTCA) System, 1.5625 µM concentration was determined as IC50 dose. This concentration was applied to all other parameters and anticancer activities were observed.